PENINGKATAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN MAKE A MATCH : PENINGKATAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN MAKE A MATCH - suhartati, suhartati; Munawar, Ali (LPMP Provinsi DKI Jakarta, 2024)
The purpose of this study was to improve social studies content learning outcomes through the make a match learning model in class VI students of SD Negeri Bleber 1 in the 2022/2023 academic year. The subjects of this study were students of class VI at SD Negeri Bleber 1 Prambanan who are located at Karanggede, Sumberharjo, Prambanan, Sleman, Yogyakarta Special Region. The type of research used was Classroom Action Research which lasted for two cycles, each cycle consisting of two meetings. The data collection instruments used were observation sheets and written tests. The data analysis technique used is a qualitative descriptive analysis to improve social studies learning outcomes. The results showed that the application of the make a match learning model could improve the learning outcomes of class VI students at SD Negeri Bleber 1. This can be seen from the percentage of implementation of learning by teachers in cycle I of 71.4% and included in the